Digital Tools in English Language Learning: Navigating Strategies and Challenges - Vanesa Agatha Indria Putri; Ginanjar Anjaniputra, Agung (Journal of English Education and Linguistics, 2025)
This systematic literature review explores the strategies and challenges involved in integrating technology into the English learning process, with a focus on the perspectives of teachers and students. Although many studies have highlighted the benefits of technology in English teaching and learning, systematic reviews that compile strategies and challenges from both teacher and student perspectives are still limited. Both perspectives are crucial, as teachers determine pedagogical implementation and students respond to technology in learning practice. This study analyzes17 peer-reviewed journal articles published between 2022 and 2025and synthesizing key findings on how strategies and challenges of digital tools in English language teaching and learning. These studies reveal that technology offers substantial benefits such as increased engagement, creativity, and accessibility, but its implementation faces various obstacles. These obstacles include limited ICT proficiency, insufficient administrative and technical support, infrastructure deficiencies (particularly in rural settings), low levels of digital literacy, student autonomy issues, and concerns over academic integrity. Educators have adopted adaptive strategies including ongoing professional development, peer collaboration, reflective teaching practices, and blended learning models to address these barriers, while the students form peer support networks to improve their digital learning experiences. This review highlights the importance of a comprehensive, multi-levelapproach that combines individual skill development with systemic infrastructure, policy support, and inclusive educational practices. In conclusion, this review calls for a shift from mere technology adoption to a deeper pedagogical transformation.